1991
DOI: 10.1002/ar.1092300416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basicranial flexion on larynx and hyoid position in rats: An experimental study of skull and soft tissue interactions

Abstract: The mammalian upper respiratory tract is a functionally dynamic region involved in respiration, deglutition, and phonation. As the structures of this area (e.g., larynx, hyoid) are suspended from the basicranium, changes in basicranial shape may affect both their anatomy and function. Although skeletal/soft tissue relationships have been examined through descriptive, comparative anatomy, these relationships have remained largely unexplored via experimental study. In this study, mechanical relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…While their study primarily focused on the larynx and was operationalized from the opposite perspective (i.e., basicranium influences upper airway), it is still broadly corroborated by findings reported here. It seems unlikely that the relationship can ever be teased apart into cause and effect since the experiments needed on human subjects are prohibited and while experiments on model species (Reidenberg and Laitman, 1991) are informative, they are rarely convincing when interpreted into terms of human morphology and physiology. In other words, we may never discover whether it is the basicranium that influences the pharynx or the pharynx that influences the basicranium.…”
Section: Table 2 Landmarks and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…While their study primarily focused on the larynx and was operationalized from the opposite perspective (i.e., basicranium influences upper airway), it is still broadly corroborated by findings reported here. It seems unlikely that the relationship can ever be teased apart into cause and effect since the experiments needed on human subjects are prohibited and while experiments on model species (Reidenberg and Laitman, 1991) are informative, they are rarely convincing when interpreted into terms of human morphology and physiology. In other words, we may never discover whether it is the basicranium that influences the pharynx or the pharynx that influences the basicranium.…”
Section: Table 2 Landmarks and Measurementsmentioning
confidence: 99%
“…The study also sets out to test two corollary hypotheses. These are that cranial base flexion drives a relative inferior displacement of the hyoid within the neck (Reidenberg and Laitman, 1991), and that external and internal cranial base angles are structurally independent (Ross and Henneberg, 1995;Lieberman and McCarthy, 1999;Lieberman et al, 2001).…”
mentioning
confidence: 99%
“…Not only is the larynx attaining a positional setting that first accomplishes an intranarial larynx, but contiguous portions of the skull base, the de facto roof of the upper respiratory tract, also appear to be undergoing considerable remodeling [17,20]. This may be significant as the shape of the basicranium has been shown both comparatively and experimentally to bear a direct relationship to the location of the larynx in the neck [21,22]. In essence, what may be beginning at this time is a remodeling and refinement of the positional anatomy of the entire upper respiratory region--soft tissue structures such as the larynx, and skeletal framework such as the skull base--in order to provide the anatomical framework for the newborn's upper respiratory and digestive tract.…”
Section: Prenatal To Early Postnatal Development Of the Upper Human Rmentioning
confidence: 99%
“…Research in our laboratory has shown that the exocranial shape of the basicranium in extant (i.e., living) mammals bears a direct relationship to the location in the neck of upper respiratory/upper digestive structures [14,21,22,37]. In particular, the degree of exocranial flexion of the basicranium is related to the location in the neck of the larynx, tongue, and pharyngeal muscles.…”
Section: Evolution Of the Upper Respiratory Tract In Human Ancestorsmentioning
confidence: 99%
“…• Strait 67 stresses that it is difficult, at present, to test the hypotheses linking the shape of the skull base and speech (Lieberman et al 43 ; Reidenberg and Laitman 54 ), because of the methodological difficulty in evaluating speech.…”
Section: Influence Of Ventilation and Languagementioning
confidence: 99%